Generation of Four-Wave Mixing in a Highly Non-Linear Optical Fiber Using a Tunable Dual Wavelength Fiber Laser Source - Zalkepali @ Zulkefli, Noor Ummi Hazirah Hani; Awang, Noor Azura; Abdul Hadi, Fatin Shaqira; Azmi, Atiqah Nabiha; Zakaria, Zahariah (Journal of Science and Technology, 2018)
In this paper, we demonstrate a Four Wave Mixing (FWM) effect in a highly nonlinear single mode optical fiber. A tunable dual-wavelength fiber laser is used to provide the pump and signal probe to generate partially degenerate FWM. Calculations using coupled differential equations and experimental results in the generation of FWM were analyzed. We observed that FWM conversion efficiency depends more significantly on the wavelength detuning between pump and signal wavelength as compared to zero-dispersion wavelength. The tunability is achieved using an arrayed waveguide grating which provides different wavelength combinations of the dual-wavelength fiber laser output and can be tuned from 1530.47nm to 1548.61nm with a spacing of 100GHz. The highly nonlinear fiber has a nonlinear coefficient, Î³ of 10.8 W-1km-1. Hence, to achieve higher FWM output power the pump power of the dual wavelength fiber laser has to be higher than that of the signal probe. The optimum measured values of pump and signal power are +13.3dBm and +5dBm respectively, limited buy the current experimental setup.